The effect of ethical leadership on good corporate governance and work effectiveness - Robertus Gunawan; Widodo Widodo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Work effectiveness greatly determines organizational performance, so its existence needs serious attention. Therefore, this study aims to investigate the effect of ethical leadership on work effectiveness mediated by good corporate governance (GCG). The participants comprised 434 employees in Indonesia's consumer goods, finance, trade, services, and investment industry across Jakarta, West Java, and Banten. Data collection was carried out using a Likert scale questionnaire. Data analysis uses path analysis supported by descriptive and correlational analysis. The result indicated that ethical leadership directly affects GCG and work effectiveness, GCG  directly affects work effectiveness, and ethical leadership indirectly affects work effectiveness mediated by GCG. The evidence confirms a new empirical model as a novelty regarding the effect of ethical leadership on employee work effectiveness mediated by GCG. This model can be used as material for exciting discussions among academics and researchers by considering several important issues relevant to this research results' limitations.